2009
DOI: 10.1063/1.3132862
|View full text |Cite
|
Sign up to set email alerts
|

Cubic Sc1−xAlxN solid solution thin films deposited by reactive magnetron sputter epitaxy onto ScN(111)

Abstract: Reactive magnetron sputter epitaxy was used to deposit thin solid films of Sc1−xAlxN (0≤x≤1) onto MgO(111) substrates with ScN(111) seed layers. Stoichiometric films were deposited from elemental Sc and Al targets at substrate temperatures of 600 °C. The films were analyzed by Rutherford backscattering spectroscopy, elastic recoil detection analysis, x-ray diffraction, and transmission electron microscopy. Results show that rocksalt structure (c)-Sc1−xAlxN solid solutions with AlN molar fractions up to ∼60% ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 37 publications
4
44
0
Order By: Relevance
“…11 In Ref. 20, the zinc-blende B3, structure was found to be considerably higher in energy as compared to cubic and wurtzite phases for Sc 0.5 Al 0.5 N and is thus excluded from this analysis. The cubic solid solution has been considered over the whole concentration range 0 Յ x Յ 1, the wurtzite in the range 0.375Յ x Յ 1 and the hexagonal structure over the range 0 Յ x Յ 0.5.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In Ref. 20, the zinc-blende B3, structure was found to be considerably higher in energy as compared to cubic and wurtzite phases for Sc 0.5 Al 0.5 N and is thus excluded from this analysis. The cubic solid solution has been considered over the whole concentration range 0 Յ x Յ 1, the wurtzite in the range 0.375Յ x Յ 1 and the hexagonal structure over the range 0 Յ x Յ 0.5.…”
Section: Resultsmentioning
confidence: 99%
“…We have thus reported that AlN molar fractions of up to ϳ60% can be dissolved into c-Sc 1−x Al x N͑111͒, epitaxially deposited onto a ScN͑111͒ seed layer. 20 Higher AlN contents result in phase separation into wurtzite structure ͑w͒-AlN or AlN-rich w-Sc 1−x Al x N, with up to four epitaxial relationships to the seed layer. Akiyama et al reported on textured Sc 1−x Al x N thin films, with 0.54Յ x Յ 1, deposited by reactive rf dual-magnetron sputtering onto Si͑001͒ substrates.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus the importance of the two control factors is not statistically accepted. Journal of the Ceramic Society of Japan 118 [12] 1166-1169 2010…”
Section: Resultsmentioning
confidence: 99%
“…For the (S)TEM-EDX measurements, a ~3 Å electron probe was used. [25,26], the presented alloys display considerably higher mixing enthalpies. Since Sc and Y share a similar electronic bonding behaviour, the larger volume difference between YN and AlN as compared to that between ScN and AlN is likely to be the major contributor to this finding.…”
Section: Methodsmentioning
confidence: 99%